PHẢN ỨNG GHÉP GLYCIDYLMETACRYLAT LÊN POLYETYLEN PHẦN II. ẢNH HƯỞNG CỦA THÀNH PHẦN HÓA HỌC ĐẾN PHẢN ỨNG GHÉP - Thuỷ, Nguyễn Thị; Tùng, Nguyễn Huy; Chương, Bùi (Vietnam Journal of Chemistry, 2012)
The influence of dicumyl peroxide (DCP), glycidyl methacrylate (GMA) and styrene on the effiency of grafting reaction of GMA on polyethylene (PE) was studied. The results showed at DCP content of 0.5 phr the highest grafting yield was obtained while the MFI and contact angle reached the smallness values. The grafting yield, MFI and contact angle were found to be optimum for the GMA content of 12 phr. The molar ratio styrene with GMA made grafting yield increased from 1.999%wt to 3.354 %wt